Nitrogen abundance in the X-ray halos of clusters and groups of galaxies - Mao, Junjie; de Plaa, Jelle; Kaastra, Jelle S.; Pinto, Ciro; Gu, Liyi; Mernier, François; Yan, Hong-Liang; Zhang, Yu-Ying; Akamatsu, Hiroki (Astronomy and astrophysics (Berlin), 2019)
Context. Chemical abundances in the X-ray halos (also known as the intracluster medium, ICM) of clusters and groups of galaxies can be measured via prominent emission line features in their X-ray spectra. Elemental abundances are footprints of time-integrated yields of various stellar populations that have left their specific abundance patterns prior to and during the cluster and group evolution. Aim. We aim to constrain nitrogen abundances in the CHEmical Evolution RGS Sample (CHEERS), which contains 44 nearby groups and clusters of galaxies, to gain a better understanding of their chemical enrichment. Method. We examined the high-resolution spectra of the CHEERS sample and took various systematic effects in the spectral modelling into account. We compared the observed abundance ratios with those in the Galactic stellar populations and also with predictions from stellar yields (low- and intermediate-mass stars, massive stars, and degenerate stars). Results. The nitrogen abundance can only be well constrained (≳3σ) in one cluster of galaxies and seven groups of galaxies. The [O/Fe] – [Fe/H] relation of the ICM is comparable to that for the Galaxy, while the [N/Fe] and [N/O] ratios of the ICM are both higher than in the Galaxy. Future studies on nitrogen radial distributions are required to tell whether the obtained higher [N/Fe] and [N/O] ratios are biased as a result of the small extraction region (r/r500 ≲ 0.05) that we adopt here. Since abundances of odd-Z elements are more sensitive to the initial metallicity of stellar populations, accurate abundance measurements of N, Na, and Al are required to better constrain the chemical enrichment in the X-ray halos of clusters and groups of galaxies.